Comparative study of female sexual dysfunction in infertile couples due to male factor and female factor infertility - Dina Abdelaziz Elemam; Ahmed Abdelhady; Fadia Hassan Ali Zyada; Medhat Amer Kamel (Cairo : Dina Abdelaziz Elemam, 2017)
Objective: The present study was performed to compare female sexual dysfunction, anxiety and depression among infertile couples due to male factor and female factor infertility. Methods: Group I: 100 female with male factor infertility and group II: 100 female with female factor infertility that was assessed by medical history and investigations. Both groups were subjected to female Sexual Function Index (FSFI), beck depression inventory (BDI) and Beck anxiety inventory (BAI). Results: the 2 groups were comparable in demographic characteristics. Positive correlations with statistical significance between anxiety/depression and all variables among female factor group except for the correlation between anxiety and depression that shows no statistically significant difference. However, there were statistically significant negative correlation between sexual dysfunction and depression, and anxiety among infertile couples due to male factor(P<0.05). The higher percentage was for the female factor group with 46% are suffering from severe degree of anxiety while 35% of the male factor group are suffering the same degree. Conclusion: Sexual problems including desire, orgasm, and arousal are prevalent in females with female factor infertility, while depression and anxiety are more prevalent among females with male factor infertility. Duration of infertility is a significant predictor for female sexual dysfunction for both groups
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Andrology and STDs
Issued also as CD
Keywords: Depression; Female factor infertility; Male factor infertility